2020
DOI: 10.1109/tasc.2020.2972210
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Performance of the First Two Prototype 4.5 m Long Nb3Sn Low-β Quadrupole Magnets for the Hi-Lumi LHC Upgrade

Abstract: The U.S. High-Luminosity LHC Accelerator Upgrade Project (HL-LHC AUP) team is collaborating with CERN in the design and fabrication of the first 4.5 m long MQXFA magnets, a 150 mm aperture high-field Nb3Sn quadrupole magnet that uses the aluminum shell-based bladder-and-key technology. The first two prototype magnets, MQXFAP1 and MQXFAP2, were assembled and tested while the first pre-series structure (MQXFA03) was in fabrication. This paper summarizes the mechanical performance of these prototype structures ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…This was demonstrated by using the piecewise reference axis which considered the fiducials on the magnet. Dedicated survey measurements on the assembly table showed that the table deformed with the magnet [34]. This contributed to the magnet deformation and will be corrected [34].…”
Section: Relative Change Of the Main Field Twist Anglementioning
confidence: 99%
See 1 more Smart Citation
“…This was demonstrated by using the piecewise reference axis which considered the fiducials on the magnet. Dedicated survey measurements on the assembly table showed that the table deformed with the magnet [34]. This contributed to the magnet deformation and will be corrected [34].…”
Section: Relative Change Of the Main Field Twist Anglementioning
confidence: 99%
“…It has nominally the same mechanical structure as the first prototype magnet featuring eight separate aluminum shells [3]. No mid-plane shim or asymmetric radial shim was used thanks to the relatively uniform coil size [34].…”
Section: Coordinate Systemmentioning
confidence: 99%
“…The second prototype (MQXFAP2) demonstrated poor training and limited performance because of a fractured aluminum shell. MQXFAP2 test data were presented in [7], [20] and a detailed analysis of fracture causes and preventive actions was published in [21]. Here we present a short list of the causes, which lead to this issue: 1) the design of the MQXFAP2 aluminum shells included small rounding (3 mm radius) at cutout corners, 2) a vendor made an error during fabrication resulting in "sharp corners" on one side of an end shell, 3) this non-conformity was accepted based on past LARP experience, 4) a small design change, successfully used on some short models, increased the end shell pre-load during cooldown.…”
Section: Lesson Learned About Design Criteriamentioning
confidence: 99%
“…This paper is concerned with quench test results only; other testing operations and results are reported in [7]- [9]. Therefore, the instrumentation most relevant to this discussion are the voltage taps and signals produced by them during quenches.…”
Section: Experimental Instrumentation and Pro-ceduresmentioning
confidence: 99%
“…b. Shell alignment cut-outs are now to have 10 -15 mm radius at the corners to minimize stress there [7], [12]. 3) MQXFAP1b Coil P03 failure:…”
Section: Lessons Learned and Mitigationsmentioning
confidence: 99%